Grid Analysis Display System (GrADS) and Multi Modus Visualization in Earth Science Learning Mastery and Spiritual Aspect to Enhance Concept - JOHAN, Henny; SUHANDI, Andi; WULAN, Ana Ratna; SIPRIYADI (Journal of Turkish Science Education, 2018)
The aim of this study was to enhance the student’s concept mastery and embedded spiritual attitude in the learning of earth science with the help of visualizations and authentic data analysis using GrADS. 23 pre-service physics teachers in Bengkulu, Indonesia participated in this study. This study used mixed methods with embedded experiment design. Multiple choice questions were used to collect the concept mastery data; questionnaires and open ended questions were used to collect data about spirituality attitude. The students’ testimonials about the learning program were explored by using open ended questions. The multiple choice questions were analyzed quantitatively while the observation, questionnaire, and open ended questions were analyzed qualitatively. The results show that the students’ concept mastery improve from no mastery to mastery with the average N-gain being 0.8 (high). The students got implicit values that had an impact on their spirituality of awareness and belief in the divinity of God. Similar research about embedding the spiritual aspect in the learning of earth science has not been reported widely